Answer:
- When t = 0, d = 0
- When t = 3, d = 6
- When t = 5, d = 10
Concept:
Here, we need to understand the idea of evaluation.
When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.
Solve:
PART ONE: Find d when t = 0
Given expression
d = 2t
Substitute value into the expression
d = 2 (0)
d = 0
PART TWO: Find d when t = 3
Given expression
d = 2t
Substitute value into the expression
d = 2 (3)
d = 6
PART THREE: Find d when t = 5
Given expression
d = 2t
Substitute value into the expression
d = 2 (5)
d = 10
Hope this helps!! :)
Please let me know if you have any questions